Penggunaan Alsintan Pada Pertanian Modern Dalam Usahatani Padi Sawah Untuk Mendukung Ketahanan Pangan Di Kabupaten Tangerang - Indrayanti, Temy; Prayoga, Adi; Zakky, Mochamad (Jurnal Ketahanan Nasional, 2024)
ABSTRACTModern agriculture is a more advanced agricultural system, starting from land processing technology, plant maintenance, pest and disease control, to harvest and post-harvest activities. Modern agriculture with the use of agricultural tools and machinery can increased productivity and business efficiency. The aim of this research was to determine the performance of modern agricultural businesses compared to conventional farming.This study used experimental and survey methods. The experimental method was used for the purpose of collecting data on the application of modern agriculture, while the survey method was used to collect data on the application of conventional agriculture. The sample used in this study was determined purposively as many as 40 people, namely farmers who farm rice conventionally. The analysis used was descriptive analysis by calculating the costs and income of rice farming and comparing the implementation of modern agriculture and conventional agriculture.Based on the results of the financial analysis, the costs of modern rice farming were still relatively high compared to conventional farming, but the production results obtained by modern rice farming were relatively higher compared to conventional farming. This was because the use of combine harvester can reduce the risk of damage and loss of yields on the land.